THE EFFECT OF ROA, EPS AND DER ON THE STOCK PRICE AT PT BANK MEGA TBK - Setriel Killa; Dina Ramba; Jemi Pabisangan Tahirs (CV. Four Son Scholarship, 2023)
The purpose of this study was to find out how ROA, EPS and DER affect stock prices at PT Bank Mega Tbk in 2020 - 2022. The research method used in this research is a quantitative research. In this study, the type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange. Return On Assets is calculated by comparing net income with total assets, then Earning Per Share is calculated by comparing net income with the number of outstanding shares. The Dept to Equity Ratio is calculated by comparing total debt and total equity. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that simultaneously ROA, EPS and DER affect stock prices